Initial management of hydatidiform mole. Case report - María Cuaresma-González; Laura Barrero-Real; Elena García-García; Lucía Pérez-Gallego; Julio Alberto Gobernado-Tejedor; Marta Ibáñez-Nieto (Case Reports)
Abstract